Penggunaan Aplikasi Seluler dalam Pemberian Medikasi pada Anak untuk Mencegah Kesalahan Pemberian Medikasi (Medication Error) - Anita Rachmawati; Sigit Mulyono (Journal of Telenursing (JOTING), 2023)
The purpose of this study was to analyze the use of mobile applications to assist in administering the medication needed to children to avoid the risk of errors in medication administration (medication errors). This research method uses a literature study by using a review of research journal articles that were searched through online database searches: Proquest, SAGE Journal, Clinical Key Nursing, PubMed, EBSCO, and Scopus, which were published in 2018-2022, with the keywords mobile application, drug medication, pediatric and medication error. The study's results prove that mobile applications in medication calculations can be used as an intervention to prevent medication errors in children. In conclusion, using mobile applications to administer medication to avoid medication errors in children is very useful. Keywords: Cellular Application, Dosage Calculation, Children, and Medication Error